Estimation of adequacy of mathematical models for calculation of density gasoline pairs - Іванов, С.В.; Бойченко, С.В.; Григоренко, І.В. (Proceedings of National Aviation University (archive), 2004)
This article describes existing mathematical models for calculation of density pair gasoline, and also conclusions concerning a choice of most adequate of them are made.